Combining multiple investigative approaches to unravel functional responses to global change in the understorey of temperate forests - Landuyt, Dries; Perring, Michael P; Blondeel, Haben; De Lombaerde, Emiel; Depauw, Leen; Lorer, Eline; Maes, Sybryn L; Baeten, Lander; Bergès, Laurent; Bernhardt-Römermann, Markus; Brūmelis, Guntis; Brunet, Jörg; et al. (Global change biology, 2024)
Plant communities are being exposed to changing environmental conditions all around the globe, leading to alterations in plant diversity, community composition, and ecosystem functioning. For herbaceous understorey communities in temperate forests, responses to global change are postulated to be complex, due to the presence of a tree layer that modulates understorey responses to external pressures such as climate change and changes in atmospheric nitrogen deposition rates. Multiple investigative approaches have been put forward as tools to detect, quantify and predict understorey responses to these global-change drivers, including, among others, distributed resurvey studies and manipulative experiments. These investigative approaches are generally designed and reported upon in isolation, while integration across investigative approaches is rarely considered. In this study, we integrate three investigative approaches (two complementary resurvey approaches and one experimental approach) to investigate how climate warming and changes in nitrogen deposition affect the functional composition of the understorey and how functional responses in the understorey are modulated by canopy disturbance, that is, changes in overstorey canopy openness over time. Our resurvey data reveal that most changes in understorey functional characteristics represent responses to changes in canopy openness with shifts in macroclimate temperature and aerial nitrogen deposition playing secondary roles. Contrary to expectations, we found little evidence that these drivers interact. In addition, experimental findings deviated from the observational findings, suggesting that the forces driving understorey change at the regional scale differ from those driving change at the forest floor (i.e., the experimental treatments). Our study demonstrates that different approaches need to be integrated to acquire a full picture of how understorey communities respond to global change.
Keywords: Forests; Nitrogen; plant height; lesy; forest management; resurvey study; climate change; mesocosm experiment; nitrogen deposition; rostliny; stromy; SLA; forestREplot; Plants; ekosystém; Ecosystem; Trees; herbaceous layer; dusík